2005
DOI: 10.1099/mic.0.28066-0
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of expression of type I signal peptidases in Listeria monocytogenes

Abstract: The role of type I signal peptidases (SPases I) is to remove the signal peptides of preproteins exported by the general secretory pathway. The genome of Listeria monocytogenes contains a locus encoding three contiguous SPases I (denoted SipX, SipY and SipZ). The authors recently showed that SipX and SipZ perform distinct functions in protein secretion and bacterial pathogenicity. Here, the regulation of sip gene expression in broth and in infected eukaryotic cells was studied. The results show that expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…177 Independent studies have then identified nearly 160 L. monocytogenes EGD-e genes whose expression is directly or indirectly dependent on PrfA. 92,[178][179][180][181][182] …”
Section: Regulation Of Virulence Determinantsmentioning
confidence: 99%
“…177 Independent studies have then identified nearly 160 L. monocytogenes EGD-e genes whose expression is directly or indirectly dependent on PrfA. 92,[178][179][180][181][182] …”
Section: Regulation Of Virulence Determinantsmentioning
confidence: 99%
“…We have shown previously that the expression of the sip locus is regulated by two different promoters, P sipX and P sipZ , producing a large transcript covering the entire locus (sipX-lmo1273) and a shorter one compatible with a transcription starting upstream of sipZ (sipZ-lmo1273) (Bonnemain et al, 2004;Raynaud & Charbit, 2005). Notably, the genomic organization and DNA sequence of the locus are highly conserved in the other sequenced Listeria genomes, including in L. innocua and in the recently sequenced genome of L. welshimeri .…”
Section: Results Lmo1273 Encodes An Rnase H Homologuementioning
confidence: 99%
“…We have previously identified a five-gene locus, designated sip (lmo1269-lmo1273), in the genome of L. monocytogenes EGD-e, encoding three paralogous type I signal peptidases (SPases I) (Bonnemain et al, 2004) involved in bacterial virulence. We showed that this locus was under the control of two distinct promoters, one preceding lmo1269 (designated sipX) and a second preceding lmo1271 (designated sipZ) (Raynaud & Charbit, 2005). The two distal genes of the locus (lmo1272 and lmo1273), which are co-transcribed with the SPase I genes (Raynaud & Charbit, 2005), encode proteins sharing significant similarities with the YlqF and RnhB proteins, respectively, of Bacillus subtilis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations